AN UNUSUAL INJURY FROM TOOTHBRUSH: A CASE REPORT - Yadav, Deepak; Tripathi, Shashank; Mishra, Ravish; Kandel, Laxmi; Karna, Saurav; Kandel, Santosh (Journal of Universal College of Medical Sciences, 2018)
Tooth brush plays a vital role in the maintenance of oral health and dental hygiene. Regular brushing is widely advocated by dental surgeon in terms of decreasing dental caries and periodontal problems. Though, there has been decrease in diseases due to sequale of poor oral hygiene, at the same time there are also inherent risk of accidental trauma to the surrounding soft tissue during the act of brushing, more commonly when handled by children. This paper presents a case report of a penetrating toothbrush trauma embedded in buccal soft tissue which required surgical intervention in a child patient Journal of Universal College of Medical Sciences Vol. 6, No. 1, 2018, Page: 66-68